Local Perceptions of the Forms, Timing and Causes of Behavior Change in Response to the AIDS Epidemic in Zimbabwe - Muchini, Backson (2011)
Quantitative studies indicate that HIV incidence in Zimbabwe declined since the late 1990s, due in part to behavior change. This qualitative study, involving focus group discussions with 200 women and men, two dozen key informant interviews, and historical mapping of HIV prevention programs, found that exposure to relatives and close friends dying of AIDS, leading to increased perceived HIV risk, was the principal explanation for behavior change. Growing poverty, which reduced men’s ability to afford multiple partners, was also commonly cited as contributing to reductions in casual, commercial and extra-marital sex. HIV prevention programs and services were secondarily mentioned as having contributed but no specific activities were consistently indicated, although some popular culture influences appear pivotal. This qualitative study found that behavior change resulted primarily from increased interpersonal communication about HIV due to high personal exposure to AIDS mortality and a correct understanding of sexual HIV transmission, due to relatively high education levels and probably also to information provided by HIV programs.